Inborn errors of immunity associated with characteristic phenotypes - Maine Luellah Demaret Bardou; Marina Teixeira Henriques; Anete Sevciovic Grumach (Elsevier, 2021)
Objectives: The aim of the report is to describe the main immunodeficiencies with syndromic characteristics according to the new classification of Inborn Errors of Immunity. Data source: The data search was centered on the PubMed platform on review studies, meta-analyses, systematic reviews, case reports and a randomized study published in the last 10 years that allowed the characterization of the several immunological defects included in this group. Data synthesis: Immunodeficiencies with syndromic characteristics include 65 immunological defects in 9 subgroups. The diversity of clinical manifestations is observed in each described disease and may appear early or later, with variable severity. Congenital thrombocytopenia, syndromes with DNA repair defect, immuno-osseous dysplasias, thymic defects, Hyper IgE Syndrome, anhidrotic ectodermal dysplasia with immunodeficiency and purine nucleoside phosphorylase deficiency were addressed. Conclusions: Immunological defects can present with very different characteristics; however, the occurrence of infectious processes, autoimmune disorders and progression to malignancy may suggest diagnostic research. In the case of diseases with gene mutations, family history is of utmost importance.